Menjaga Kemerdekaan Berserikat dan Kebebasan Berpendapat Sebagai Hak Warga Negara Dalam Konstitusi - Abustan (CV. Dalle’ Deceng Abeeayla, 2025)
The purpose of this research is to determine and explain that freedom of association and freedom of expression for Indonesian citizens are enshrined in Article 28 of the 1945 Constitution of the Republic of Indonesia. The research method used is empirical legal research, namely examining written law in the literature and then connecting it to real-life events. The data collection technique used library research. This research found that, even during the current administration, the implementation of freedom of expression has consistently given rise to differing interpretations and/or suggestions from law enforcement officials. In fact, citizens who express their opinions in the form of criticism or input to institutions face legal challenges for allegedly defaming the institution. This reality demonstrates the vulnerability of human rights and democracy violations within the fabric of society, the nation, and the state. Therefore, the importance of the Constitutional Court as the guardian of the constitution, specifically upholding citizens' right to freedom of expression, is paramount.